2018
DOI: 10.3390/en12010071
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production from Coffee Mucilage in Dark Fermentation with Organic Wastes

Abstract: One of primary issues in the coffee manufacturing industry is the production of large amounts of undesirable residues, which include the pericarp (outer skin), pulp (outer mesocarp), parchment (endocarp), silver-skin (epidermis) and mucilage (inner mesocarp) that cause environmental problems due to toxic molecules contained therein. This study evaluated the optimal hydrogen production from coffee mucilage combined with organic wastes (wholesale market garbage) in a dark fermentation process. The supplementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…In this work, we have demonstrated that even relatively small differences in lignin content can result in considerably increased sugar production, which supports the dissimilarity of bagasse lignin content and its effects on cellulose digestibility. The increased glucose yields with the addition of BSA helped to decrease the inhibition of non-productive absorption of cellulose enzymes onto lignin and solid residual lignin fractions.Molecules 2020, 25, 623 2 of 12 biofuel production [4,[6][7][8][9][10]. In particular, the physical barrier of lignin prevents enzyme access to cellulose and hemicellulose.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we have demonstrated that even relatively small differences in lignin content can result in considerably increased sugar production, which supports the dissimilarity of bagasse lignin content and its effects on cellulose digestibility. The increased glucose yields with the addition of BSA helped to decrease the inhibition of non-productive absorption of cellulose enzymes onto lignin and solid residual lignin fractions.Molecules 2020, 25, 623 2 of 12 biofuel production [4,[6][7][8][9][10]. In particular, the physical barrier of lignin prevents enzyme access to cellulose and hemicellulose.…”
mentioning
confidence: 99%
“…Molecules 2020, 25, 623 2 of 12 biofuel production [4,[6][7][8][9][10]. In particular, the physical barrier of lignin prevents enzyme access to cellulose and hemicellulose.…”
mentioning
confidence: 99%
“…In order to analyze the anaerobic fermentative performance, two-level half-factorial experiments were designed through the Minitab 16 software program (Minitab 16, Minitab Inc., State College, PA, USA), following our previous study [13]. The resulting 26 sets were performed in a 20-L bioreactor with an actual working volume of 13 L. Raw coffee mucilage samples do not require any supplements, such as carbon/nitrogen nutrients and initial microbial culture, for transforming fermentable sugars in the substrate to hydrogen since there are appropriate nutrient sources, minerals, and microorganisms in the samples [13,19,20]. Our earlier work found that 7 species were isolated after anaerobic dark fermentation, and 4 species (Micrococcus luteus, Kocuria kristinae, Streptococcus uberis, and Brevibacillus laterosporus) were relatively highly involved and participated in hydrogen production.…”
Section: Experimental Design and Data Collectionmentioning
confidence: 99%
“…Our earlier work found that 7 species were isolated after anaerobic dark fermentation, and 4 species (Micrococcus luteus, Kocuria kristinae, Streptococcus uberis, and Brevibacillus laterosporus) were relatively highly involved and participated in hydrogen production. Furthermore, increased hydrogen yield was observed when co-cultivation (bacterial consortium) was applied with K. kristinae and S. uberis, suggesting that the bacterial population could change the metabolic pathways and/or biochemical/molecular interactions that lead to efficient dark fermentation [13]. Briefly, a two-level factorial experimental test was designed with three different ratios (w/w) of coffee mucilage and organic wastes mixture (8:2, 5:5, and 2:8) were prepared, and additional control runs with only coffee mucilage or organic wastes were added [13].…”
Section: Experimental Design and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation